PSUDOKAPASITOR 2D BERBASIS NANOMATERIAL NIKEL-KOBALT FOSFAT (NIXCOY(PO4)3) UNTUK MENINGKATKAN KINERJA SUPERKAPASITOR HIBRIDA - Khoiri, Miftahul
Supercapacitors are advanced electrochemical energy storage devices that have higher energy density and capacitance than conventional capacitors and produce more power than batteries. So, electrodes were developed to increase energy density. In this research, nickel-cobalt phosphate has been developed as a positive electrode or pseudocapacitor for hybrid supercapacitor applications. Nickel-cobalt phosphate was synthesized in different Ni:Co ratios, namely 1:0, 5:1, 3:1, 2:1, 1:1, and 1:2. The formation process of NiCo phosphate bimetal involved synthesizing nickel-cobalt glycerate as a precursor combined with triethyl phosphate (TEP) as a phosphate source, followed by calcination at 600 °C for 2 hours in air atmosphere. Morphological analysis revealed that nickel-cobalt glycerate exhibited solid spherical structures, nickel-cobalt TEP showed mushroom-like and disc-like structures, while nickel-cobalt phosphate displayed nut-like and cracker-like structures. Nickel-cobalt phosphate possessed an amorphous phase, indicating a large surface area which is advantageous for supercapacitor applications. The specific capacitance values from electrochemical testing showed that the nickel-cobalt phosphate electrodes for all variations were 673 Fg-1, 1211 Fg-1, 1123 Fg-1, 982 Fg-1, 948 Fg-1, and 510 Fg-1 respectively at a current density of 1 Ag-1 in 6 M KOH solution. The specific capacitance results were supported by BET analysis, which showed surface areas of 12, 48, 44, 43, 40, and 34 m²g-1 respectively. Meanwhile, the Ni5Co1(PO4)3/AC hybrid supercapacitor demonstrated a specific capacitance of 34 Fg-1 at 1 Ag-1, with energy and power densities of 11 WhKg-1 and 750 WKg-1 respectively.